Developing expressed sequence tags (ESTs) from polymorphic transcript-derived fragments (TDFs) in cassava (Manihot esculenta Crantz) - Suarez, MC; Bernal, A.; Gutiérrez, J.; Tohme, Joseph M.; Fregene, Martin A. (Canadian Science Publishing, 2000)
We applied the cDNA-AFLP (amplified fragment length polymorphism) technique to mRNA from the parents of a cassava (Manihot esculenta) genetic mapping population, and obtained more than 500 transcript-derived fragments (TDFs) that were unique in either parent. A subset of 50 TDFs were cloned and sequenced. Sequence alignment of the expressed sequence tags (ESTs) revealed mostly genes of unknown function. Six of the TDFs were mapped on to the cassava genetic map. We also demonstrated by genetic mapping of the TDFs, as RFLP (restriction fragment length polymorphism) markers, that TDFs are more polymorphic than random cDNAs. Generation of ESTs as differentially expressed sequences, in time or between different varieties, is proposed as a way of developing ESTs around specific traits for the candidate locus approach to mapping complex traits.